The transcriptional repressor Blimp1/Prdm1 regulates postnatal reprogramming of intestinal enterocytes. - Harper, J; Mould, A; Andrews, R; Bikoff, E; Robertson, E (2011)
Female mammals produce milk to feed their newborn offspring before teeth develop and permit the consumption of solid food. Intestinal enterocytes dramatically alter their biochemical signature during the suckling-to-weaning transition. The transcriptional repressor Blimp1 is strongly expressed in immature enterocytes in utero, but these are gradually replaced by Blimp1(-) crypt-derived adult enterocytes. Here we used a conditional inactivation strategy to eliminate Blimp1 function in the developing intestinal epithelium. There was no noticeable effect on gross morphology or formation of mature cell types before birth. However, survival of mutant neonates was severely compromised. Transcriptional profiling experiments reveal global changes in gene expression patterns. Key components of the adult enterocyte biochemical signature were substantially and prematurely activated. In contrast, those required for processing maternal milk were markedly reduced. Thus, we conclude Blimp1 governs the developmental switch responsible for postnatal intestinal maturation.